Empires ascendant : 400 BC-AD 200 - Time-Life Books (Amsterdam : Time-Life Books, 1988)
1. History, Ancient.
Includes bibliographical references.
Bibliography: p. 168-169.
1. History, Ancient.
Keywords: History, Ancient